PENINGKATAN HASIL BELAJAR SISWA KELAS 2A PADA MATERI PENJUMLAHAN MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) - Muwasa’ah; Sandha Soemantri; Sayyidati Marlinda Yunita (PROCEEDING UMSURABAYA, 2024)
This research employed the Classroom Action Research (CAR) method. Data collection procedures involved written tests and observations. The analysis revealed that the learning outcomes in mathematics, specifically addition, showed improvement by implementing the Project-Based Learning (PjBL) approach. The post-test results in cycle I showed a 81% achievement among students, and after interventions in cycle II, the post-test indicated an increased proficiency rate of 92%. Based on the research analysis conducted on the mastery of addition operations among 2nd-grade students at SDN Penjaringansari I/271 in cycle II using the Project-Based Learning (PjBL) model, and considering the discussion on the lower mastery level of addition operations among IIA students, it can be concluded that the implementation of Project-Based Learning (PjBL) in the learning process effectively enhances the learning outcomes of 2A students, particularly in the area of addition operations.